THE INFLUENCE OF TEACHER’S TEACHING SKILLS TOWARD STUDENTS’ ACHIEVEMENT IN ENGLISH SUBJECT - Mukmin Mukmin; Junira Yepeikene (BABASAL English Education Journal, 2020)
This research aimed to determine the influence of teacher’s teaching skills toward students’ achievement in English subject in class IXa of SMP Negeri 6 Luwuk. Data analysis methods in this research include descriptive statistics, data normality test and Pearson product moment test. The test results in this research found that the calculated r counted of 0.735 > r table 0.374, meaning that there was a significant influence between the teaching skills of teacher toward students achievement in English subject in class IXa SMPN 6 Luwuk. r counted of 0.735 or 73.5% indicates the level of a strong relationship between teacher’s teaching skills and students’ achievement. R square value showed that the influence of teacher’s teaching skills toward students’ achievement is 54.0% while 46.0% is influenced by other variables not included in this research. Therefore from the results of the data obtained that there is an influence between teacher’s teaching skills toward students’ achievement in English subject with the influence is 54.0% and a high level of strong relationship that is 73.5%.